Sabidurías y mitos que tienen las mujeres en edad fértil sobre menopausia en el Barrio San Vicente de la ciudad de Loja - Correa Conde, Carmen Mercedes (2015)
The Menopause is an event that indicates the beginning of a new evolutionary stage in the life of women, characterized by present physiological, psychological, social and cultural changes; it is a transition period that ends the reproductive capacity of women. The research called KNOWLEDGE AND MYTHS ABOUT THE MENOPAUSE OF WOMEN IN THE EMERALD North Neighborhood, is a descriptive study, that pursued objectives like the identification of the knowledge and myths about menopause in women of childbearing age who live in this neighborhood during the period of September 2014 to Julio 2015, and wich were the ways and means of communication that helped them to acquire these knowledges. The universe consisted of 169 women of childbearing age; The instrument used was the survey and presentation of the data was performed on simple frequency tables, the analysis was based on the literature referred to in the theoretical framework and the following results were obtained; Women who participated in the research are among 20-39 years. About the knowledge of menopause, the study population with grade secondary schooling and higher education knows about it. Regarding the myths about menopause, women with grade of primary, secondary and higher education, manifest that in this period the reproductive organs atrophy, experienced ailments and increased risk of developing breast cancer. The source of information were family, friends and medical consultation was a minimum percentage. Keywords: Menopause; knowledge; myths.